Pendampingan Terhadap Anak Korban Kekerasan Berbasis Gender Di Kabupaten Bengkalis - Sumarni, Titin; Sopiani, Ika Kurnia; Mufaro’ah (Cattleya Darmaya Fortuna, 2025)
This community service aims to collect data on victims of violence against children in the Districts of Mandau, Rupat and Rupat Urata, and to assist victims of violence against children. The results of this dedication are case data in three sub-districts in Bengkalis Regency, namely Mandau District, Rupat District and North Rupat District, so data on cases of gender-based violence against children can be obtained in 2022, namely: In Mandau District there is 1 person, namely: 16 year old female with sexual harassment and rape cases, 1 person in Rupat District, namely: 11 year old female with sexual harassment case, 3 cases of sexual harassment in Rupat Utara District, namely 13 year old female with obscenity and rape cases, 13 year old male 13 years old with physical and psychological violence cases, 13 year old female with physical and psychological violence cases. The assistance carried out includes: Case Data Collection, Case Chronology Assessment, Assisting Victims to make reports at the Mandau Police, Conducting Counseling with the LK3 Alhi Team (Counselors) Against Victims, Together with the LK3 Expert Team (Counselors) Conducting Counseling to their parents and Closest Relatives, Referring Clients (Victims) to the Al-Ghasyiyah Orphanage to receive Guidance and Education.